2016
DOI: 10.2522/ptj.20160054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Virtual Reality Training on Balance and Gait Ability in Patients With Stroke: Systematic Review and Meta-Analysis

Abstract: The results suggest that VR training is more effective than balance or gait training without VR for improving balance or gait ability in patients with stroke. Future studies are recommended to investigate the effect of VR on participation level with an adequate follow-up period. Overall, a positive and promising effect of VR training on balance and gait ability is expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
163
0
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(190 citation statements)
references
References 64 publications
9
163
0
18
Order By: Relevance
“…It is still debatable that which of the characteristics of virtual reality have greater impact, it is also unclear that effects of the characteristics are adequate in long term. de Rooij et al [7] also supported the evidence that VR training is more beneficial than conventional balance or gait training [7]. The study of Silva et al [8] revealed that virtual reality parallel with kinesiotherapy and learning transfer exercises had an efficacious impact on stroke individuals [8].…”
Section: Discussionsupporting
confidence: 56%
“…It is still debatable that which of the characteristics of virtual reality have greater impact, it is also unclear that effects of the characteristics are adequate in long term. de Rooij et al [7] also supported the evidence that VR training is more beneficial than conventional balance or gait training [7]. The study of Silva et al [8] revealed that virtual reality parallel with kinesiotherapy and learning transfer exercises had an efficacious impact on stroke individuals [8].…”
Section: Discussionsupporting
confidence: 56%
“…With the use of outcome measures on participation level it can be investigated whether potential improvements induced by VR training translate to real life. In the available literature the effect of virtual training on daily life activity and participation level is not yet established [15].…”
Section: Discussionmentioning
confidence: 99%
“…Since VR training is characterised by individualised, high intensity training in a variety of virtual environments with a high amount of real-time feedback [13][14][15] it might be valuable in stroke rehabilitation. This is confirmed by recent studies [12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…bezpieczeństwa pacjenta) byłyby niemożliwe do przeprowadzenia w prawdziwym świecie [14]. Zaletą treningu z wykorzystaniem VR jest wysoki poziom powtarzalności ćwiczeń przy jednoczesnej różnorodności treningu, pozwalający na zmniejszenie poczucia wysiłku [15]. Istotny jest dobór właściwych, specyficznych ćwi-czeń, które są dostosowane do indywidualnych potrzeb pacjenta [5].…”
Section: Rehabilitacja Funkcji Ruchowychunclassified